2021
DOI: 10.3390/md19050251
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Alzheimer’s Molecules Derived from Marine Life: Understanding Molecular Mechanisms and Therapeutic Potential

Abstract: Alzheimer’s disease (AD) is a devastating neurodegenerative disease and the most common cause of dementia. It has been confirmed that the pathological processes that intervene in AD development are linked with oxidative damage to neurons, neuroinflammation, tau phosphorylation, amyloid beta (Aβ) aggregation, glutamate excitotoxicity, and cholinergic deficit. Still, there is no available therapy that can cure AD. Available therapies only manage some of the AD symptoms at the early stages of AD. Various studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 137 publications
(155 reference statements)
1
21
0
Order By: Relevance
“…A previous study showed that Bryo possessed a significant neuroprotective effect. 16 The Bryo treatment group in this study also showed similar therapeutic effects in the cuprizone-induced model. In addition, Bryo encapsulated by exosomes further enhanced its neuroprotective effect.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…A previous study showed that Bryo possessed a significant neuroprotective effect. 16 The Bryo treatment group in this study also showed similar therapeutic effects in the cuprizone-induced model. In addition, Bryo encapsulated by exosomes further enhanced its neuroprotective effect.…”
Section: Resultssupporting
confidence: 63%
“…Bryo is a natural product derived from the marine invertebrate Bugula neritina . 16 Previously, it was believed to have potent and broad anti-tumor and anti-inflammation activities. 24,45 Recently, Kornberg et al showed that Bryo has an apparent therapeutic activity for demyelinating diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, bryostatin-1 is commercially obtained by synthesis. Cancer is the main area of research of bryostatin-1 and its derivatives, with studies including applications in apoptotic restoration, multidrug-resistance circumvention, immune system stimulation, and drug synergism [ 184 ]. The low concentration of bryostatins in bryozoans (i.e., a final yield of 0.00014% after extraction) makes extraction unviable for large-scale production [ 143 ].…”
Section: Isolation Of High-value Molecules With Neuroprotective Effects Against Alzheimer’s Diseasementioning
confidence: 99%
“…It has also been proposed that WA is the α,β-unsaturated ketone in ring A of common withanolides and may be produced through the sequence 20–23 [ 45 ]. Three sites are prone to Michael addition alkylation reactions and nucleophilic attacks, namely the unsaturated A-ring at C3, the epoxide structure at C5, and the E-ring at the C24 position [ 47 ]. Depicted in Figure 1 is the biosynthesis of WA.…”
Section: Biosynthesis Of Withaferin a (Wa)mentioning
confidence: 99%